PEMBELAJARAN MEMBACA PERMULAAN PADA SISWA KELAS II SDN 009 CIKADUT DENGAN MENGGUNAKAN PENDEKATAN TEKNIK PERMAINAN MELENGKAPI CERITA - Martiana, Tina; Rahayu, Galih Dani Septiyan (IKIP Siliwangi, 2021)
This study aims to examine the pre-reading learning of grade II students using game techniques to complement online-based stories. The research method used is descriptive qualitative. The subjects in this study were students of class II SD Negeri 009 Cikadut, Bandung City with 32 students consisting of 13 male students and 19 female students. The instruments used were teacher and student observation sheets, questions about completing the story, and teacher and student questionnaires. The results showed that there was an increase in the quality of learning when the application of game techniques complemented the story. This is indicated by the mean value of reading comprehension at the beginning of the class of 80.63 which is classified as in the good category, the highest score of students is 96 and the lowest score is 62. Students' learning completeness shows that 84.0% of students get scores above the minimum completeness criteria and 16 , 0% still scored below the minimum completeness criteria value